2020
DOI: 10.1002/alz.036167
|View full text |Cite
|
Sign up to set email alerts
|

NeuroEPO in mild‐to‐moderate Alzheimer’s disease

Abstract: Background NeuroEPO, is a nasal pharmaceutical solution of recombinant human erythropoietin with low sialic acid. Methods Phase II/III, prospective, double‐blind, randomized, placebo‐controlled, multicenter with adaptive design clinical trial involving patients with mild‐to‐moderate Alzheimer’s. NeuroEPO or placebo, with doses 0.5 or 1.0 mg 3 times a week for 48 weeks was administered by nasal route. The primary outcome measure was a score on the 11‐item cognitive subscale of the Alzheimer’s disease Assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Preclinical studies have demonstrated the effects of NeuroEPO on CNS protection in models of Alzheimer's, stroke, and glutamate-induced excitotoxicity (6)(7)(8)(9). In clinical studies, intranasal administration has shown to be safe and well tolerated in healthy volunteers and shows favorable effects with clinical improvement in patients with Parkinson's disease, Alzheimer's, and spinocerebellar ataxia type 2 (10)(11)(12)(13)(14). In addition, NeuroEPO has beneficial effects on glycemia and reproduction in diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies have demonstrated the effects of NeuroEPO on CNS protection in models of Alzheimer's, stroke, and glutamate-induced excitotoxicity (6)(7)(8)(9). In clinical studies, intranasal administration has shown to be safe and well tolerated in healthy volunteers and shows favorable effects with clinical improvement in patients with Parkinson's disease, Alzheimer's, and spinocerebellar ataxia type 2 (10)(11)(12)(13)(14). In addition, NeuroEPO has beneficial effects on glycemia and reproduction in diabetic rats.…”
Section: Introductionmentioning
confidence: 99%